The Griffin Sisters' greatest hits : a novel [large type] - Weiner, Jennifer (Thorndike Press large print top shelf., 2025)
"Sisters Cassie and Zoe Grossberg could not have been more different. Zoe yearned for fame; Cassie was a musical prodigy who preferred the safety of the shadows. On the brink of adulthood in the early 2000s, destiny catapulted the sisters into the spotlight as the pop sensation the Griffin Sisters. But after a whirlwind year, the band abruptly broke up. Two decades later, the sisters aren't speaking, and the real reason for the Griffin Sisters' breakup is still a mystery. Zoe's teenage daughter, Cherry, is on a quest to learn the truth about what happened. As secrets emerge, can they forgive each other--and themselves?"--